The form of the firm a normative political theory of the corporation - Singer, Abraham A. (New York Oxford University Press, 2019)
"What are we to make of the power that corporations wield over people? Is such power legitimate? Many think so. To many businessmen and economists, as well as the general public, firms are purely private and economic entities, justified in using all legal means to maximize profit. In The Form of the Firm, Abraham A. Singer contends that such a view rests on a theoretical foundation that, while quite subtle, is deeply flawed. Contrary to the conventional wisdom, corporations are not natural outgrowths of the free market. Instead, Singer invites us to see corporations as political institutions that correct market inefficiencies through mechanisms normally associated with government - hierarchy, power, and state-sanctioned authority. Corporations exist primarily to increase economic efficiency, but they do this in ways that distinguish them from the markets in which they operate. Corporations serve economic ends, but through political means. Because of this, Singer argues that they also must be structured and obliged to uphold the social and political values that enable their existence and smooth-running in the first place: individual autonomy, moral and social equality, and democratic norms and institutions. A profound and timely rethinking of what a corporation actually is and how power within it ought to be structured and exercised, The Form of the Firm will reshape our understanding of political theory, corporate governance, corporate law, and business ethics" -- Back cover.
Introduction -- A framework for a political theory of the corporation -- The economic theory of corporate efficiency and justice -- The classical theories of the corporation -- Ronald Coase and the difference between markets and firms -- The managerial challenge to liberalism -- The Chicago School's theory of the corporation -- From market to firm to market again -- The concept of "norm-governed productivity" -- Corporate justice within efficiency horizons -- Toward a relational corporate law -- The architecture of corporate governance and workplace democracy -- Business ethics and efficiency: the market failures approach -- Business ethics and equality: the concept of "justice failure" -- Conclusion.
Includes bibliographical references and index.
Keywords: Corporate governance; Corporations